Waste segregation through recycle and composting activities among the community in urban and suburban areas / Norhafezah Kasmuri and Siti Nurhafizah Abdull Razak - Kasmuri, Ts. Dr. Norhafezah; Abdull Razak, Siti Nurhafizah (2021)
The number of wastes generated in Malaysia is increasing every year. Eighty per cent of solid waste in landfills comes from recycled material, and food waste production increases 15 000 tons per day. Recyclable waste and food waste are the highest waste that produces in the landfill. Recycling and food composting are two solutions that can reduce waste and slow down the rate of waste received at the landfill. This research aims to determine the level of knowledge and awareness on waste segregation through recycling and composting. It identifies the top reason for not applying waste segregation and encouraging the community in urban and suburban areas. An online questionnaire has been distributed to the community in urban and suburban areas in Selangor and Johor. A total of 125 respondents participated in this study. The survey analysis found no significant difference in the level of knowledge in waste segregation through recycling and composting between urban and suburban areas. Generally, the respondent has a basic understanding and awareness of waste segregation, although only a few respondents have not practiced recycling due to several highlighted constraints. Therefore, installing reverse vending machines (RVM), organizing campaigns, and providing more information on waste segregation are the top choices to encourage waste segregation among the community. Moreover, further study needs to be extended to the household group in other states and assessing the effectiveness of RVM will visualize the segregation behaviours among the community.